Upaya Meningkatkan Kemampuan Komunikasi Dua Arah Anak dengan Gangguan Spektrum Autis melalui Media Flip Chart - Iin Yulita; Yulvia Sani; Annisa Purwanggi (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2026)
This study was motivated by the low level of two-way communication skills among children with Autism Spectrum Disorder (ASD), particularly in the aspects of eye contact, responsiveness, and turn-taking during conversations. The study aimed to describe two-way communication skills before intervention, analyze the implementation of flip chart media, and determine its effectiveness in improving two-way communication skills. A Single Subject Research (SSR) approach with an A–B–A design consisting of baseline-1, intervention, and baseline-2 phases was employed. The participant was a first-grade child with Autism Spectrum Disorder at SLB Negeri Sidomulyo. Data were collected through observation and performance tests and analyzed using visual analysis within and across conditions. The results showed that communication skills in the baseline-1 phase were at a moderate level (44.4%–50%), increased to a high level during the intervention phase (66.6%–83.3%), and remained at a high level during the baseline-2 phase (77.7%–83.3%). The findings indicate that flip chart media can be used as an alternative visual learning medium to improve two-way communication skills in children with Autism Spectrum Disorder and serve as a reference for special education practitioners.